Laser Efficiency Enhancement Due to Non-Resonant Feedback in Dye-Doped Hybrid Materials: Theoretical Insights and Experiment - Cerdán, Luis; Costela, Angel; García-Moreno, Inmaculada; Martin, Virginia; Perez-Ojeda Rodriguez, Maria Eugenia (IEEE Journal of Quantum Electronics, 2011)
It has been recently shown that the presence of nanoscatterers up to a certain density, homogeneously distributed in gain media, instead of being detrimental to conventional two-mirror cavity laser efficiency and directionality, may result in an increase of the output energy due to an enlargement in the effective optical path. Here we present a theoretical model for the stimulated emission in very weak scattering active media and show that the aforementioned laser efficiency improvement owes to a contribution of non-resonant feedback due to Rayleigh scattering. The model reveals that a critical factor in the physics of the emission is the nanometric size of the scattering particles irrespective of their nature. Experiments are carried out and the results are shown to be in agreement with the predictions of the model.
Keywords: Hybrid materials; lasers; rate equations; scattering